Soybean SPX1 is an important component of the response to phosphate deficiency for phosphorus homeostasis. (July 2016) - Zhang, Jingyao; Zhou, Xi; Xu, Ying; Yao, Minlei; Xie, Fengbin; Gai, Junyi; Li, Yan; Yang, Shouping
Highlights: GmSPX1 could negative controls transcription of Pi starvation responsive genes indirectly. The elongation and number of root hairs was suppressed by overexpression of GmSPX1 . The yeast two-hybrid assays and BiFC assays demonstrated that GmSPX1 could interact with GmMYB48. GmMYB48 is a new phosphate starvation induced transcription factor, and the interaction of GmSPX1/GmMYB48 can be considered a potential candidate suppressor. Abstract: Phosphate (Pi) homeostasis is required for plant growth and development, but the Pi-signaling pathways in plants still remain largely unknown. Proteins only containing the SPX domain are very important in phosphate (Pi) homeostasis and signaling transduction. In the T-DNA insertion Arabidopsis mutant spx3, AtPHT1-4, AtPHT1-5, AtACP5, AtRNS, and AtAT4 expression levels were increased under Pi-sufficient condition and low Pi condition compared with WT. Meanwhile, the expression levels of these phosphate starvation genes was inhibited in OXSPX1 and spx3 /OXSPX1 compared with WT, only under Pi-sufficient condition. These imply that GmSPX1 may negatively control the transcription of Pi starvation responsive genes indirectly. However, there were no differences between expression levels of these PSI genes in spx3 and those in WT under −Pi conditions. These facts imply that the negative regulation of GmSPX1 and AtSPX3 on PSI genes is depending on Pi concentration. Consistent with this, GmSPX1 overexpression in the WT and spx3 decreased the total Pi concentration in plants and changed root hair morphology, suppressing the elongation and number of root hairs compared with the WT and spx3 . The yeast two-hybrid assays and BiFC assays demonstrated that GmSPX1 could interact with GmMYB48.The qRT-PCR analysis showed that GmMYB48 is a new phosphate starvation induced transcription factor in soybean. Also, GmSPX1 overexpression led to decreased transcripts of AtMYB4, an ortholog of GmMYB48, in OXSPX1. Together, these results suggest that GmSPX1 is a negative regulator in the Pi signaling network of soybean, and the interaction of GmSPX1/GmMYB48 can be considered a potential candidate suppressor.